Evolving tiger beetle (Coleoptera: Cicindelidae) conservation research: reconciling perspectives from amateurs and professionals - Fernando Fernández; Thorsten Assmann; Deokjea Cha; Leonardo Lopes Costa; Jörg Gebert; Grey Gustafson; C. Barry Knisley; Payal Molur; David L. Pearson; Michael J. Samways; Vinita Sangela; Jürgen Wiesner (Journal of Insect Conservation, 2026)

Habitat diversity and peat moss cover drive the occurrence probability of the threatened ground beetle Carabus menetriesi (Coleoptera: Carabidae) in a Bavarian mire - Ingmar Harry; Thorsten Assmann; Carsten F. Dormann; Carl J. Skarbek (Journal of Insect Conservation, 2022)
Within the Natura 2000 network, there is a legal imperative to protect endangered species. A lack of knowledge about habitat requirements for these species undermines the ability to make informed decisions about appropriate conservation measures, especially for isolated populations that may have developed habitat preferences specific to their region. Carabus menetriesi is an endangered ground beetle found in Europe and warrants protection under EU law. We collected occupancy data of C. menetriesi using live pitfall traps over two seasons in 2016 and 2018 at a protected nature reserve in southern Bavaria, Germany. Here, we present the results of a patch-occupancy modeling approach to determine habitat preferences for C. menetriesi at this site. Our model shows that increasing Sphagnum cover and habitat diversity led to higher occupancy levels for C. menetriesi at this site, while tree cover was negatively correlated with occupancy, but increased the detectability of the species. Implications for insect conservation Measures for protecting the C. menetriesi population at the study site were taken in accordance with our results. Areas with high tree cover were thinned at several sites, although the success of this measure has yet to be determined. Our findings about habitat diversity suggest that expansion of low intensity grazing in the area, a measure that was suggested as a result of our survey and is currently in process of implementation, might benefit the species. Whether our results can be transferred to C. menetriesi populations in different habitats remains to be investigated, however, our methodological approach with regard to both the data collection and analysis can be used to assess other populations and provide important information about relevant habitat parameters for that population. This will allow conservation managers to make well-informed decisions about conserving C. menetriesi, or indeed other similar carabid species with isolated populations.

Conservation value of semi-open habitats for ground beetles (Coleoptera: Carabidae, Cicindelidae) in Central Europe - Estève Boutaud; Dorothea Nolte; Ingmar Harry; Thorsten Assmann; Claudia Drees (Biodiversity and Conservation, 2022)
Reintroduction of grazing to counteract insect decline will lead to an increase of semi-open habitats. Semi-open habitats are highly heterogeneous, consisting of a mosaic of patches of trees or shrubs embedded in a matrix dominated by dwarf shrubs or grasses. Despite a lack of evidence, structural heterogeneity is expected to allow many species to co-occur, making semi-open habitats appear highly valuable for invertebrate conservation. We studied ground beetles in eight sites in two landscapes of Central Europe each encompassing semi-open, open, and forest habitats. Rapid response to environmental change and limited dispersal abilities make ground beetles an excellent model taxon to evaluate the effectiveness of such conservations measures. In both studied landscapes, ground beetle assemblages in semi-open habitats tended to be distinct and intermediate between those from the forest and open habitats. Species richness and functional diversity in semi-open habitats were similar to open habitats at site level. The majority of species entered the semi-open habitats, except for most threatened species, yet, few species were exclusively associated with semi-open habitats. We conclude that the continuous presence of many species in semi-open habitats likely results from mass effects rather than habitat heterogeneity per se . Our findings underline the conservation value of the existing forest, heathland, and grassland habitats over semi-open habitats which can, however, function as dispersal habitats and increase landscape connectivity. Strategies aiming at promoting semi-open habitats to counteract insect decline should target enhancing connectivity rather than the creation of habitats only.

Land-use legacy and tree age in continuous woodlands: weak effects on overall ground beetle assemblages, but strong effects on two threatened species - Marietta Hülsmann; Estève Boutaud; Jörn Buse; Andreas Schuldt; Thorsten Assmann (Journal of Insect Conservation, 2019)

Habitat specialization, distribution range size and body size drive extinction risk in carabid beetles - Dorothea Nolte; Estève Boutaud; D. Johan Kotze; Andreas Schuldt; Thorsten Assmann (Biodiversity and Conservation, 2019)

The pace of range expansion: a long-term study on the flightless ground beetle Carabus hortensis (Coleoptera: Carabidae) - Eva Völler; Estève Boutaud; Thorsten Assmann (Journal of Insect Conservation, 2018)

Molecular analyses and species distribution models indicate cryptic northern mountain refugia for a forest‐dwelling ground beetle - Claudia Drees; Martin Husemann; Katharina Homburg; Patric Brandt; Petra Dieker; Jan C. Habel; Henrik von Wehrden; Pascale Zumstein; Thorsten Assmann (Journal of Biogeography, 2016)
Aim Identification of potential glacial refugia and post‐glacial colonization processes of a flightless, cold‐adapted ground beetle Location Central and eastern Europe. Methods We analysed the genetic structure of 33 Carabus sylvestris populations sampled across its entire distribution range using nuclear and mitochondrial markers. We further compiled occurrence records to develop species distribution models to predict distribution ranges for the last glacial period and the present based on the species’ current climatic niche. Results Distinct genetic lineages were detected for a number of mountain ranges and were congruent for both molecular marker systems. Most genetic splits were the results of vicariance, whereas dispersal was rare. Our models suggest that the species’ distribution range was larger and more interconnected in the past. Main conclusions Our data support multiple glacial refugia for C. sylvestris , some of which were located north of the Alps. Some lower mountain ranges were likely recolonized post‐glacially.

Evolutionarily significant units in a flightless ground beetle show different climate niches and high extinction risk due to climate change - Katharina Homburg; Patric Brandt; Claudia Drees; Thorsten Assmann (Journal of Insect Conservation, 2014)

Woody plant phylogenetic diversity mediates bottom–up control of arthropod biomass in species-rich forests - Andreas Schuldt; Martin Baruffol; Helge Bruelheide; Simon Chen; Xiulian Chi; Marcus Wall; Thorsten Assmann (Oecologia, 2014)

Tree diversity promotes functional dissimilarity and maintains functional richness despite species loss in predator assemblages - Andreas Schuldt; Helge Bruelheide; Walter Durka; Stefan G. Michalski; Oliver Purschke; Thorsten Assmann (Oecologia, 2014)

Long-Term Trends in Tree-Ring Width and Isotope Signatures (δ13C, δ15N) of Fagus sylvatica L. on Soils with Contrasting Water Supply - Werner Härdtle; Thomas Niemeyer; Thorsten Assmann; Saskia Baiboks; Andreas Fichtner; Uta Friedrich; Anne C. Lang; Burkhard Neuwirth; Laurent Pfister; Christian Ries; Andreas Schuldt; Natalie Simon; et al. (Ecosystems, 2013)

A suite of multiplexed microsatellite loci for the ground beetle Abax parallelepipedus (Piller and Mitterpacher, 1783) (Coleoptera, Carabidae) - Tamar Marcus; Thorsten Assmann; Walter Durka; Claudia Drees (Conservation Genetics Resources, 2013)

Climatic responses of tree-ring width and δ13C signatures of sessile oak (Quercus petraea Liebl.) on soils with contrasting water supply - Werner Härdtle; Thomas Niemeyer; Thorsten Assmann; Armin Aulinger; Andreas Fichtner; Anne Lang; Christoph Leuschner; Burkhard Neuwirth; Laurent Pfister; Markus Quante; Christian Ries; Andreas Schuldt; et al. (Plant Ecology, 2013)

Allele elimination recalculated: nested subset analyses for molecular biogeographical data - Jan Christian Habel; Werner Ulrich; Thorsten Assmann (Journal of Biogeography, 2013)
Aim Post‐glacial colonization of species from low‐latitude refugia to high latitudes, or from lower to higher elevations, often involves repeated founder effects due to stepwise colonization. This may cause repeated population bottlenecks and the subsequent loss of alleles. Regression analyses have traditionally been used to analyse the correlation between the mean numbers of alleles and geographical distances from refugia. Here, we describe and evaluate the performance of nested subset analyses for detecting allele elimination. Methods Genetic data sets from five butterfly and one beetle species were reanalysed using regression and nested subset analyses. Results The data sets analysed here showed both congruent and divergent results under regression and nested subset analyses. Some data sets did not feature a significant correlation between the mean number of alleles and the colonization trajectory, but did show significant nested structure. Others showed the opposite effects. Using allele frequencies from the same data sets, we did not obtain significant patterns of nestedness. Main conclusions Our results indicate that classical regression analyses are not always a suitable tool for analysing allele elimination, and nestedness analyses are much more meaningful. Local natural selection can alter allele frequencies, thereby erasing biogeographical patterns that have evolved as a result of the stochastic processes involved in colonization. Thus, an appropriate means of documenting allele elimination sensu Reinig is the joint application of nested subset and regression analyses based on presence/absence and abundance data for genetic diversity.

Low genetic diversity of a high mountain burnet moth species in the Pyrenees - Petra Dieker; Claudia Drees; Thomas Schmitt; Thorsten Assmann (Conservation Genetics, 2013)

Plant traits affecting herbivory on tree recruits in highly diverse subtropical forests - Andreas Schuldt; Helge Bruelheide; Walter Durka; David Eichenberg; Markus Fischer; Wenzel Kröber; Werner Härdtle; Keping Ma; Stefan G. Michalski; Wolf‐Ulrich Palm; Bernhard Schmid; Erik Welk; et al. (Ecology Letters, 2012)
Differences in herbivory among woody species can greatly affect the functioning of forest ecosystems, particularly in species‐rich (sub)tropical regions. However, the relative importance of the different plant traits which determine herbivore damage remains unclear. Defence traits can have strong effects on herbivory, but rarely studied geographical range characteristics could complement these effects through evolutionary associations with herbivores. Herein, we use a large number of morphological, chemical, phylogenetic and biogeographical characteristics to analyse interspecific differences in herbivory on tree saplings in subtropical China. Unexpectedly, we found no significant effects of chemical defence traits. Rather, herbivory was related to the plants' leaf morphology, local abundance and climatic niche characteristics, which together explained 70% of the interspecific variation in herbivory in phylogenetic regression. Our study indicates that besides defence traits and apparency to herbivores, previously neglected measures of large‐scale geographical host distribution are important factors influencing local herbivory patterns among plant species.

Genetic erosion in habitat specialist shows need to protect large peat bogs - Claudia Drees; Pascale Zumstein; Thorsten Buck-Dobrick; Werner Härdtle; Andrea Matern; Hartmut Meyer; Goddert von Oheimb; Thorsten Assmann (Conservation Genetics, 2011)

Genetic erosion in a stenotopic heathland ground beetle (Coleoptera: Carabidae): a matter of habitat size? - Claudia Drees; Henk De Vries; Werner Härdtle; Andrea Matern; Markus Persigehl; Thorsten Assmann (Conservation Genetics, 2011)

Value of Semi‐Open Corridors for Simultaneously Connecting Open and Wooded Habitats: a Case Study with Ground Beetles - BRITTA EGGERS; ANDREA MATERN; CLAUDIA DREES; JAN EGGERS; WERNER HÄRDTLE; THORSTEN ASSMANN (Conservation Biology, 2010)
To counteract habitat fragmentation, the connectivity of a landscape should be enhanced. Corridors are thought to facilitate movement between disconnected patches of habitat, and linear strips of habitat connecting isolated patches are a popular type of corridor. On the other hand, the creation of new corridors can lead to fragmentation of the surrounding habitat. For example, heathland corridors connect patches of heathland and alternatively hedgerows connect patches of woodland. Nevertheless, these corridors themselves also break up previously connected patches of their surrounding habitat and in so doing fragment another type of habitat (heathland corridors fragment woodlands and woodland strips or hedgerows fragment heathlands). To overcome this challenge we propose the use of semi‐open habitats (a mixture of heathland and woodland vegetation) as conservation corridors to enable dispersal of both stenotopic heathland and woodland species. We used two semi‐open corridors with a mosaic of heathland and woody vegetation to investigate the efficiency of semi‐open corridors for species dispersal and to assess whether these corridors might be a suitable approach for nature conservation. We conducted a mark‐recapture study on three stenotopic flightless carabid beetles of heathlands and woodlands and took an inventory of all the carabid species in two semi‐open corridors. Both methodological approaches showed simultaneous immigration of woodland and heathland species in the semi‐open corridor. Detrended correspondence analysis showed a clear separation of the given habitats and affirmed that semi‐open corridors are a good strategy for connecting woodlands and heathlands. The best means of creating and preserving semi‐open corridors is probably through extensive grazing .

Unprecedented long-term genetic monomorphism in an endangered relict butterfly species - Jan Christian Habel; Frank Emmanuel Zachos; Aline Finger; Marc Meyer; Dirk Louy; Thorsten Assmann; Thomas Schmitt (Conservation Genetics, 2009)

Genetic diversity and population structure of the endangered insect species Carabus variolosus in its western distribution range: Implications for conservation - Andrea Matern; Konjev Desender; Claudia Drees; Eva Gaublomme; Wolfgang Paill; Thorsten Assmann (Conservation Genetics, 2009)

Shifts in N and P Budgets of Heathland Ecosystems: Effects of Management and Atmospheric Inputs - Werner Härdtle; Goddert von Oheimb; Anna-Katharina Gerke; Marion Niemeyer; Thomas Niemeyer; Thorsten Assmann; Claudia Drees; Andrea Matern; Hartmut Meyer (Ecosystems, 2009)

Population ecology of the rare carabid beetle Carabus variolosus (Coleoptera: Carabidae) in north-west Germany - Andrea Matern; Claudia Drees; Hartmut Meyer; Thorsten Assmann (Journal of Insect Conservation, 2008)

Microsatellites and allozymes as the genetic memory of habitat fragmentation and defragmentation in populations of the ground beetle Carabus auronitens (Col., Carabidae) - Claudia Drees; Andrea Matern; Jean‐Yves Rasplus; Heinrich Terlutter; Thorsten Assmann; Friedrich Weber (Journal of Biogeography, 2008)
Aim This paper has three aims: (1) to reconstruct the population history of a flightless silvicolous (forest) ground beetle in a region where strong anthropogenic activity has altered the connectivity of the landscape; (2) to estimate the effects of both contemporary and historical landscape structure on the genetics of populations; and (3) to investigate the reasons for clinal variation in one gene locus found in an earlier study carried out in the same geographical location. Location Münster (Westphalia), north‐west Germany. Methods We investigated 26 populations of the ground beetle Carabus auronitens Fabricius, 1792 by analysing seven polymorphic microsatellite loci and an allozyme locus. Samples of at least 16 individuals per site were studied. These were obtained from dry pitfall traps placed at 23 sites and from three additional (refuge) populations. We used regression and correlation analyses to investigate the effects of both historical and contemporary landscape structure on the allele frequency distributions of the investigated loci. Spatial autocorrelation analysis was used to study possible clinal variations, and admixture rates were calculated in order to assess the genetic influence of populations from possible refuges. Possible reasons for the development of the cline were examined using simulation models. Results The allele frequency distributions at the investigated loci could not be explained by selection or isolation by distance. We found clinal variation in 50% of the investigated loci and our simulations indicated that this was unlikely to have developed by chance. Admixture rates show significant influences of the investigated refuge populations on the populations under study. Main conclusions The findings strongly suggest that the clinal variation is secondary. It results from recolonization of the area by C. auronitens from multiple refuges after anthropogenic landscape changes caused forest fragmentation and led to species isolation.

Strongly diverging population genetic patterns of three skipper species: the role of habitat fragmentation and dispersal ability - Dirk Louy; Jan Christian Habel; Thomas Schmitt; Thorsten Assmann; Marc Meyer; Paul Müller (Conservation Genetics, 2007)

Restoration ecology meets carabidology: effects of floodplain restitution on ground beetles (Coleoptera, Carabidae) - Jens Günther; Thorsten Assmann (Biodiversity and Conservation, 2005)

The ground beetle fauna of ancient and recent woodlands in the lowlands of north-west Germany (Coleoptera, Carabidae) - Thorsten Assmann (Biodiversity and Conservation, 1999)

The Effect of Habitat Changes on the Endangered Ground Beetle Carabus Nitens (Coleoptera: Carabidae) - Thorsten Assmann; Judith Janssen (Journal of Insect Conservation, 1999)